The Species Identification and Genomic Analysis of Haemobacillus shengwangii: A Novel Pathogenic Bacterium Isolated From a Critically Ill Patient With Bloodstream Infection - Du, Yingying; Li, Xuming; Liu, Yuhao; Mu, Shikui; Shen, Dandan; Fan, Shu; Lou, Zheng; Zhang, Shouqin; Xia, Han; Yuan, Yinghua; Wang, Sheng (Frontiers in Microbiology, 2022)
Since the first strain related to Thermicanaceae was reported in 1999, almost no 17 literature on Thermicanaceae is available, particularly its genomics. We recently 18 isolated a novel pathogenic bacterium, the strain DYY3, from the blood sample of a 19 critically ill patient. The morphological, physiological, and biochemical characteristics 20 of strain DYY3 were presented in this study, and the virulence factor genes and 21 antibiotic resistance of DYY3 were also determined. Interestingly, the average 22 nucleotide identity and core genes based amino acid identity analysis indicated that 23 strain DYY3 was genus novel and species novel. Moreover, based on phylogenetic 24 analysis, both 16S rRNA gene and whole genomic core gene sequences suggested that 25 strain DYY3 belonged to the family Thermicanaceae, this novel taxon was thus named 26 Haemobacills shengwangii gen. nov., sp. nov. Besides, both the whole genome-based 27 phylogenetic tree and amino acid identity analysis indicated that Thermicanus aegyptius, 28 Hydrogenibacillus schlegelii, Brockia lithotrophica and the newly discovered species 29 Haemobacills shengwangii should belong to Thermicanaceae at the family level, and T. 30 aegyptius was the closest species to H. shengwangii. We also constructed the first high-quality 31 genome in the family Thermicanaceae using next-generation sequencing and single-molecule 32 real-time sequencing technologies, which certainly contributed to further genomics studies and 33 metagenomic-based pathogenic detection in the future. 34